Fat spouses and hours of work: Are body and Pareto weights correlated? - Sonia Oreffice; Climent Quintana-Domeque (IZA Journal of Labor Economics, 2012)
We explore the relationship between relative physical attractiveness in the household and the hours worked by married men and women. Using PSID data, we find that husbands who are thinner relative to their wives work fewer hours, while wives who are heavier relative to their husbands work more hours. These results are robust to controlling for individual, spousal characteristics, and conventional distribution factors, suggesting that high body weight leads to low Pareto weight in the household: fatter spouses may compensate with more hours of work. Our household bargaining interpretation is supported by the fact that we cannot statistically reject the collective proportionality restriction when including measures of the distribution of relative physical attractiveness in the population.
Keywords: D1; J1; J22; 330; Hours worked; Body mass index; Collective model; Arbeitszeit; Dauer; Körpergewicht; Geschlecht; Ehe; USA